2018
DOI: 10.3390/tropicalmed3030102
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Mobile Application to Support Peripheral Health Workers to Diagnose and Treat People with Skin Diseases in Resource-Poor Settings

Abstract: The high prevalence of skin diseases in resource-poor settings, where health workers with sufficient knowledge of skin diseases are scarce, calls for innovative measures. Timely diagnosis and treatment of skin diseases, especially neglected tropical diseases (NTDs) that manifest with skin lesions, such as leprosy, is crucial to prevent disabilities as well as psychological and socioeconomic problems. Innovative technological methods like telemedicine and mobile health (mHealth) can help to bridge the gap betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
(26 reference statements)
0
27
0
Order By: Relevance
“…Some may be useful for training. In 2017, there were more than 500 mobile applications in dermatology with a significant growth in telemedicine applications (9). One example is the SkinApp application developed to improve the management of dermatological diseases in front-line health centers.…”
Section: Technological Limitsmentioning
confidence: 99%
“…Some may be useful for training. In 2017, there were more than 500 mobile applications in dermatology with a significant growth in telemedicine applications (9). One example is the SkinApp application developed to improve the management of dermatological diseases in front-line health centers.…”
Section: Technological Limitsmentioning
confidence: 99%
“…Six (46%) studies [ 32 - 37 ] were reported to be community-based cross-sectional studies with the main objective of epidemiologically mapping a specific disease based on its clinical symptoms. Four out of 13 (31%) studies had different designs as follows: a mixed-methods approach to define challenges to be considered [ 38 ]; different implementation scenarios for a specific mHealth intervention [ 39 ]; the sustainability of an intervention [ 40 ]; and the process of developing a specific mHealth tool or assessing its usability [ 10 , 38 ]. One trial was a cross-sectional study analyzing the accuracy of a new diagnosis strategy [ 41 ], and another was a prospective cohort study testing the efficacy of an mHealth strategy in training health care workers [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various innovative methods have been used to enhance the clinical management and epidemiological surveillance of, among others, skin and infectious diseases worldwide. These include, but are not limited to, technological methods such as telemedicine, artificial intelligence, and mobile health (mHealth) [ 10 ]. mHealth has been proven to be a promising tool to improve the diagnosis and treatment of several diseases such as skin cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital interventions such as eLearning, digital diagnostics, and geolocation of leprosy patients are priorities. A number of applications are under development, including digital registries; a leprosy referral and surveillance network among healthcare providers; tele-dermatology to support health workers with access to medical specialists [ 22 ]; and, smartphone apps to facilitate diagnosis and treatment for peripheral health workers [ 23 ]. Policy to support the practical implementation of these developments will also be needed.…”
Section: Panel: the Research Priorities To Achieve Zero Leprosymentioning
confidence: 99%